ANALISIS KEMAMPUAN MEMBACA SISWA DISLEKSIA DENGAN METODE ORTON GILLINGHAM - Bajtullah, Sonia; Dewi, Galuh Kartika; Mubarok, M. Khusni (Jurnal Visi Ilmu Pendidikan, 2024)
In elementary schools that have not implemented an inclusion system, there are some students who experience difficulties in the reading process which is called dyslexia. This study aims to see how the activities and learning outcomes of dyslexic students improve reading skills using the Orton Gillingham method. The approaches and methods in this study are descriptive qualitative. Observation, interview, and documentation are techniques used to collect data and then analyzed qualitatively. The research subjects were two dyslexic students at SDN Kedunglukuk 1 Candi Sidoarjo. Based on the results of the study it can be concluded that the learning activities of dyslexic students during learning using the Orton Gillingham method can make dyslexic students motivated and active during learning activities while the learning outcomes of dyslexic students using the Orton Gillingham method can improve reading skills, because the learning process involves all the senses so that it can make it easier for students memorize letters. The Orton Gillingham method is considered very helpful in facilitating dyslexic students in the process of learning to read.